Hubungan Antara Usia Balita, Pemberian ASI dan Daerah Tempat Tinggal dengan Kejadian Diare pada Balita di Indonesia - Fenny Putri Maharani; Lailatul Muniroh; Chrysoprase Thasya Abihail (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Diarrhea is a condition of defecation with a watery consistency and a frequency of more than three times per day. The prevalence of diarrhea among toddlers in Indonesia reached 11% based on the 2018 Riskesdas data. Diarrhea can be caused by several factors, including internal and external factors. Internal factors that contribute to diarrhea include the age of the toddler and breastfeeding practices. External factors that can cause diarrhea stem from environmental factors including socioeconomic factors. This study aims to analyze the relationship between the age of toddlers, breastfeeding practices, and geographical location with the incidence of diarrhea among toddlers in Indonesia. This study was a secondary data with a cross sectional design. The study sample consist of the entire population of women of reproductive age (WRA) who toddlers within the last five years prior to the 2017 IDHS, amounting to 17,848 respondents. Data were analyzed using the chi-square test and logistic regression. The results showed that there was a significant relationship between the age of toddlers (p=0.042), breastfeeding practices (p=0.000), and geographical location (p 0.000) with the incidence of diarrhea among toddlers in Indonesia. The frequency of diarrhea incidence among toddlers born within the last five years prior tothe 2017 IDHS was 14.2%. Based on the child factor, the percentage of diarrhea incidence in children under five years old is most prevalent in the 12-59 month old group (14.5%). The incidence of diarrhea in children under five is also influenced by the length of breastfeeding, the length of breastfeeding in children under five for 6-24 months (15.1%) and rural residence (15.4%).The occurrence of diarrhea among toddlers is also influenced by the duration of breastfeeding, particularly breastfeeding for 6-24 months (15.1%). In conclusion, the age of toddlers, breastfeeding practices, and geographical location have a significant relationship with the incidence of diarrhea among toddlers.